Foodways in Southern Oman - Risse, Marielle, author.
1 online resource (xviii, 197 pages)
Keywords: "Foodways in Southern Oman examines the objects, practices and beliefs relating to producing, obtaining, cooking, eating and disposing of food in the Dhofar region of southern Oman. The chapters consider food preparation, who makes what kind of food, and how and when meals are eaten. Marielle Risse connects what is consumed to themes such as land usage, gender, age, purity, privacy and generosity. She also discusses how foodways are related to issues of morality, safety, religion, and tourism. The volume is a result of fourteen years of collecting data and insights in Dhofar, covering topics such as catching fish, herding camels, growing fruits, designing kitchens, cooking meals and setting leftovers out for animals. It will be of interest to scholars from a range of disciplines, including anthropology, sociology, food studies, Middle Eastern studies and Islamic studies"--